O-Regioselective Synthesis with the Silver Salt Method - Wang, Y.-G.; Barnes, E.C. (ACS Omega, 2018)
The excellent O-regioselectivity of the glycosidation of the ambident 2-O-substituted 5-fluorouracil (5-FU) via the silver salt method is computationally investigated at the MP2/6-311++G(2d,p):DZP//B3LYP/6-31+G(d):DZP level of theory. The reactions studied are those between 1-bromo-1-deoxy-2,3,4,6-tetra-O-acetyl-α-d-glucopyranose and the silver salts of 5-FU, 2-O-butyl-5-FU, and 2-O-benzyl-5-FU. Two pathways are considered as follows: (A) one where the silver and bromide ion do not interact, and (B) another where the silver and bromide ion interact in the transition states. Because the O-reaction barriers are much lower (by 13.3-22.2 kcal/mol) than N-reaction barriers in both pathways, the O-regioselectivity of the silver salt method can be satisfactorily explained by either path A or path B. Furthermore, path B, where Ag and Br interact consistently, has lower activation barriers than the corresponding path A (by 6.8-17.4 kcal/mol) in both N- and O-reactions. This computational result can be attributed to the following reasons: (1) the speeding-up effect in Koenigs-Knorr reactions due to the addition of silver carbonate into the reaction mixture; (2) the halogens being pulled away by silver ions from halides, as proposed by Kornblum and co-workers; and (3) the oxocarbenium ion involvement in the glycosidation reactions. The large energy difference between N- and O-transition states originates from the association between Ag and N-(O-) of the ambident unit (-N3-C4=O4) that shows significant covalent character so that the O-reaction transition states of the silver salt method benefit from favorable ionic interaction (C+···O-) and favorable covalent interaction (Ag···N). These two favorable interactions are in agreement with the hard and soft acids and bases principle; the former is a hard-hard interaction and the latter is a soft-soft interaction. © 2018 American Chemical Society.
Keywords: dept.che; peer-reviewed

The Relationship between Carotid and Femoral Artery Intima-Media Thickness and Histopathologic Grade of Atherosclerosis in Patients with Chronic Kidney Disease. - Nezami, Nariman; Ghabili, Kamyar; Shokouhi-Gogani, Behrooz; Mirchi, Mohammad; Ghojazadeh, Morteza; Safa, Javid; Zomorrodi, Afshar; Gharadaghi, Abasad; Mojadidi, Mohammad Khalid; Tarzamni, Mohammad Kazem; Khajir, Ghazal; Ghorashi, Sona; et al. (Nephron, 2018)
BACKGROUND/AIMS: Variability in the grade of atherosclerosis among patients with chronic kidney disease (CKD) could affect the ultrasound measurements of intima media thickness (IMT). We sought to investigate IMTs of carotid (cIMT) and femoral (fIMT) arteries in CKD patients and assess the degree of their correlation with histopathological atherosclerosis., METHODS: Eighty-nine out of 99 enrolled subjects completed this study. The subjects were divided into 3 groups: 34 patients with CKD (Case group), 31 with coronary artery disease undergoing coronary artery bypass graft (CABG, positive control group), and 24 healthy kidney donors (negative control group). For histopathological assessment of atherosclerosis, arterial tissue samples were obtained from the patients in each study group. The cIMT and fIMTs were measured by ultrasonography., RESULTS: Histopathological atherosclerosis was present in 82.3, 100, and 20.8% of CKD, CABG, and donor groups respectively (p < 0.001). CKD patients had higher values of cIMT and fIMT than the donor group (p = 0.01 and 0.004, respectively). cIMT was positively correlated with the grade of atherosclerosis in the CKD group only (p < 0.001), while fIMT was correlated with the grade of atherosclerosis in both CKD and donor groups (p < 0.001 and p = 0.009 respectively). In CKD patients, cIMT >0.65 mm and femoral values >0.57 mm predicted the presence of histopathological atherosclerosis with sensitivities of 96 and 92% respectively., CONCLUSION: Higher values of cIMT and fIMT in CKD patients are associated with higher rates and degrees of histopathological atherosclerosis. Additionally, when compared to fIMT, cIMT has a higher sensitivity for detecting atherosclerosis in CKD patients. Copyright © 2018 S. Karger AG, Basel.
Keywords: *Atherosclerosis/pa [Pathology]; *Carotid Arteries/pa [Pathology]; *Carotid Intima-Media Thickness; *Femoral Artery/pa [Pathology]; *Renal Insufficiency, Chronic/pa [Pathology]; Adult; Article; Atherosclerosis; Atherosclerosis/co [Complications]; Carotid Arteries; Carotid Intima-Media Thickness; Chronic kidney disease; Common carotid artery; Female; Femoral Artery; Femoral artery; Histopathology; Humans; Intima media thickness; Male; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Renal Insufficiency, Chronic/co [Complications]; adult; arterial tissue; arterial wall thickness; atherosclerosis; carotid artery; chronic kidney failure; clinical trial; complication; controlled study; coronary artery bypass graft; coronary artery disease; dept.che; disease severity; echography; female; femoral artery; histopathology; human; human tissue; logistic regression analysis; major clinical study; male; middle aged; multicenter study; pathology; peer-reviewed; priority journal; prospective study; sensitivity analysis

Improved admixture vaccine of fentanyl and heroin hapten immunoconjugates: Antinociceptive evaluation of fentanyl-contaminated heroin - Hwang, Candy S.; Smith, Lauren C.; Natori, Yoshihiro; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (ACS Omega, 2018)
Fentanyl and its derivatives have become pervasive contaminants in the U.S. heroin supply. Previously, we reported a proof-of-concept vaccine designed to combat against heroin contaminated with fentanyl. Herein, we optimized the admixture vaccine and found that it surpassed the individual vaccines in every antinociceptive test, including a 10% fentanyl to heroin formulation. It is anticipated that other co-occurring drug abuse disorders may also be examined with admixture vaccines. © 2018 American Chemical Society.
Keywords: dept.che; peer-reviewed

Antibacterial Assessment of Heteroaryl, Vinyl, Benzyl, and Alkyl Tetrazole Compounds. - Dudley, Joshua; Feinn, Liana; DeFrancesco, Heather; Lindsay, Erica; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2018)
Background: In previous reports, the antibacterial properties of certain tetrazole derivatives have been described. We have previously reported the antibac...
Keywords: *Anti-Bacterial Agents/pd [Pharmacology]; *Tetrazoles/pd [Pharmacology]; 1 (1h tetrazol 5 yl)isoquinoline; 1,2 di(1h tetrazol 5 yl)ethene; 2 (1h tetrazol 5 yl)pyrazine; 4 (1h tetrazol 5 yl)pyridine; 5 (1h pyrrol 2 yl) 1h tetrazole; 5 (2 methoxybenzyl) 1h tetrazole; 5 (furan 2 yl) 1h tetrazole; 5 (naphthalen 2 ylmethyl) 1h tetrazole; 5 (pyrrol 2 yl) 1h tetrazole; 5 (thiophen 3 yl) 1h tetrazole; 5 styryl 1h tetrazole; 5-substituted 1H-tetrazoles, (3 + 2) cycloaddition; Amoxicillin; Amoxicillin/pd [Pharmacology]; Anti-Bacterial Agents; Anti-Bacterial Agents/cs [Chemical Synthesis]; Antibacterial activity; Antimicrobial activity; Article; Cerium(III) chloride heptahydrate; Escherichia coli; Escherichia coli/de [Drug Effects]; Heterocycles; Microbial Sensitivity Tests; Microwave; Molecular Structure; Pseudomonas aeruginosa; Pseudomonas aeruginosa/de [Drug Effects]; Staphylococcus aureus; Staphylococcus aureus/de [Drug Effects]; Sulfamethoxazole; Sulfamethoxazole/pd [Pharmacology]; Tetrazoles; Tetrazoles/cs [Chemical Synthesis]; Trimethoprim; Trimethoprim/pd [Pharmacology]; amoxicillin; antibacterial activity; antibiotic agent; antiinfective agent; benzilic acid derivative; carbon nuclear magnetic resonance; chemical structure; controlled study; cotrimoxazole; dept.bio; dept.che; drug effect; heating; incubation time; microbial sensitivity test; minimum inhibitory concentration; nonhuman; peer-reviewed; phenyl(1h tetrazol 5 yl)methanol; priority journal; substitution reaction; sulfamethoxazole; synthesis; tetrazole derivative; trimethoprim; unclassified drug; vinyl derivative

Undergraduate organic experiment: Tetrazole formation by microwave heated (3 + 2) cycloaddition in aqueous solution - DeFrancesco, Heather; Dudley, Joshua; Coca, Adiel (Journal of Chemical Education, 2018)
An undergraduate experiment for the organic laboratory is described that utilizes microwave heating to prepare 5-substituted 1H-tetrazole derivatives through a (3 + 2) cycloaddition between aryl nitriles and sodium azide. The reaction mixture is analyzed by thin layer chromatography. The products are purified through an acid–base extraction and recrystallization. Characterization is accomplished using melting point, infrared, 1H NMR, and 13C NMR spectroscopy. Students are tasked with determining and confirming the structure of their product based on their assigned nitrile and characterization data.
Keywords: Acids/Bases; Addition Reactions; Catalysis; Green Chemistry; Hands-On Learning/Manipulatives; Heterocycles; Inquiry-Based/Discovery Learning; Laboratory Instruction; Organic Chemistry; Second-Year Undergraduate; dept.che; peer-reviewed

Expanding quantification of arsenic in water to 0 μg L −1 with a field test kit: substituting 0.4% M/V silver nitrate as the colorimetric reagent; employing digital image analysis - Kearns, James K; Edson, Cody B (Water, Air, and Soil Pollution, 2018)
This study confronts the questionable reliability and accuracy of field test kits distributed globally to determine arsenic in drinking water. Because kits are the primary method of arsenic analysis in the areas most affected, an alternate, nontoxic formulation is needed to provide accurate results. Hypothesizing that introducing silver nitrate as the reagent in test kits could successfully substitute for restricted mercuric bromide, the study found that the reformulated kits provided reliable, precise, and accurate results over a broader range of contamination. Digital image analysis was used to examine the blue color value produced when arsine reacts with silver nitrate impregnated test strips. An optimal concentration of AgNO3 exhibiting the greatest linearity was determined by graphical comparison and the color intensity of the strips observed to be inversely proportional to the concentration of As (III). Adapted field test kits were then constructed to examine water samples ranging in arsenic contamination from 0 to 50 μg L−1. A series of reactions was completed to demonstrate reproducibility and test for the accuracy of the procedure. Statistical examination of colorimetrically quantified results confirmed the hypothesis that silver nitrate can reliably and precisely expand the kit’s range of detection while maintaining its low cost, quick assessment, and uncomplicated technique. This new method, using 0.4% m/v AgNO3 as a reagent for the Gutzeit reaction, was able to distinguish between concentrations of 0, 5, 10, 15, and 50 μg L−1 at the 95% confidence level. © 2018, Springer International Publishing AG, part of Springer Nature.
Keywords: Arsenic; Arsenic contamination; Arsenic in drinking waters; Article; Chemical reactions; Color; Colorimetric analysis; Colorimetric reagents; Colorimetry; Digital image analysis; Drinking water; Field test; Field test kit; Graphical comparison; Image analysis; Nitrates; Nitrogen compounds; Optimal concentration; Potable water; Reproducibilities; Silver; Silver compounds; Testing; Water; accuracy assessment; arsenic; chemical reaction; color; colorimetry; dept.che; digital image; digital imaging; drinking water; field test kit; image analysis; measurement accuracy; nitrate; quantitative analysis; reliability analysis; reproducibility; silver; silver nitrate; water analysis; water contamination; water pollution; water sampling

Grade perceptions of students in chemistry coursework at all levels - Webb, Jeffrey A.; Karatjas, Andrew G. (Chemistry Education Research and Practice, 2018)
Various reasons are attributed to poor student performance in physical science courses such as lack of motivation, lack of ability, and/or the overall difficulty of these courses. One overlooked reason is a lack of self-awareness as to preparation level. Through a study over a two-year period, students at all levels (freshman through M.S.) of a chemistry program were surveyed and asked to self-report predictions of their score on examinations. At all levels, strong evidence of the Kruger–Dunning effect was seen where higher performing students tended to underpredict their examination scores while the lowest performing students tended to grossly overpredict their scores.
Keywords: dept.che; peer-reviewed